Pengaruh Bauran Pemasaran Terhadap Kepuasaan Konsumen Produk PT Garuda Food - Adhar Ardiansyah; Herry Nurdin (ARBITRASE: Journal of Economics and Accounting, 2020)
The main reason a company can continue to live and thrive is with consumers. This makes consumers' decisions are a priority for all companies in the world. This study aims to determine the effect of marketing mix on consumer satisfaction of PT Garuda Food products. The type of research used is associative, the research location at the research location was conducted at the Sinar Niaga Sejahtera Office (PT. GARUDA FOOD) Bima branch, the study was conducted for 4 months. The population in this study were all consumers of PT. Garuda Food in Kec. Palibelo who had bought 125 Garuda Airlines products. The samples in this study were 95 people, the sampling technique used was purposive sampling with the Slovin formula. The research instrument used a questionnaire with a Likert scale. The type of data used is quantitative data from primary data sources. Data collection techniques are observation, interviews, questionnaires and literature study. Data analysis includes validity test, reliability test, simple linear regression analysis, simple correlation analysis, determination test and t test. The results of data analysis showed that there was an influence between the marketing mix on consumer satisfaction on Pt Garuda Food products with a tcount of 6.365 greater than the ttable value of 1.985 (6.365> 1.985) with a significance value of 0.000 less than 0.05 (0.000 <0 , 05)